Structure-dependent activity of plant natural products against methicillin-resistant Staphylococcus aureus - Moreno Cardenas, Calisto; Çiçek, Serhat S. (Frontiers in Microbiology, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the major causes for nosocomial infections and has been classified as “high priority pathogen” by the World Health Organization. Its ability to develop resistances has been a challenge for the last decades and is still a threat to health care systems, as strains with resistances to the so-call drugs of last resort have been discovered. Therefore, new antibiotics are urgently needed. Natural products are an important source for the development of new drugs, thereby mostly serving as lead compounds for further modification. In this review, the data on plant natural products with reported anti-MRSA activity until the end of 2022 is discussed, highlighting the most effective drugs with respect to their inhibitory concentrations as well as with regard to eventual synergistic effects with existing antibiotics. In the latter sense, the class of alkaloids must be mentioned, exhibiting additive or synergistic effects by inhibiting bacterial efflux pumps. With regard to the antibiotic activity, phloroglucinol derivatives certainly belong to the most promising compounds, revealing several candidates with remarkable effects, e.g., lupulone, ivesinol, rhodomyrtone, aspidinol, or hyperforin. Also, the class of terpenoids yielded noteworthy compounds, such as the sesquiterpene lactones parthenolide and lactopicrin as well as acetophenone sesquiterpenes and sphaerodiene type diterpenoids, respectively. In addition, pronounced effects were observed for the macrolide neurymenolide A and three flavonol dicoumaroylrhamnosides.